1976
DOI: 10.1136/bmj.2.6044.1100
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase in acute myocardial infarction: a controlled multicentre study in the United Kingdom.

Abstract: case ventilatory depression returns. The use of a larger dose of naloxone, given either intravenously or intramuscularly, is being investigated to determine whether the action of naloxone can be usefully prolonged.We thank the midwives, obstetricians, and paediatricians of the University Hospital of Wales for their help and co-operation in the study. There was no significant difference in the peak levels or pattern of enzyme increase. The incidence of cardiac failure and reinfarction was similar in the two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(14 citation statements)
references
References 7 publications
(1 reference statement)
0
13
0
1
Order By: Relevance
“…22 Similarly, in a randomized study comparing extended infusion of streptokinase (2500 X 10 3 IU over 24 hr) with conventional therapy in 595 patients with symptoms of myocardial ischemia of less than 24 hours duration, Aber et al reported 5 thromboembolic CNS events in each group. 23 In the absence of statistical analysis it appears that thromboembolic or other cerebrovascular events are no more frequent in the groups of unselected patients receiving thrombolytic agents systemically, than in those receiving anticoagulation or conventional therapy for acute MI.…”
Section: Acute Myocardia] Infarctionmentioning
confidence: 99%
“…22 Similarly, in a randomized study comparing extended infusion of streptokinase (2500 X 10 3 IU over 24 hr) with conventional therapy in 595 patients with symptoms of myocardial ischemia of less than 24 hours duration, Aber et al reported 5 thromboembolic CNS events in each group. 23 In the absence of statistical analysis it appears that thromboembolic or other cerebrovascular events are no more frequent in the groups of unselected patients receiving thrombolytic agents systemically, than in those receiving anticoagulation or conventional therapy for acute MI.…”
Section: Acute Myocardia] Infarctionmentioning
confidence: 99%
“…They reported an absolute decrease in mortality of 7.6% in streptokinase-treated patients compared with the control group. During the 1970s, many small, underpowered and nonrandomized trials were performed, which showed mixed results [16][17][18]. Two important clinical trials led to the eventual acceptance of IV thrombolysis for acute myocardial infarction:1) the European Cooperative Study Group for Streptokinase Treatment in Acute Myocardial Infarction [19] and 2) the Gruppo Italiano per la Sperimentazione della Streptochinasi nell'Infarto Miocardico (GISSI) trial [20].…”
Section: Thrombolytics For Acute Myocardial Infarctionmentioning
confidence: 99%
“…Left ventricular thrombus is a common (42-48%) postmortem finding in patients with acute myocardial infarction [13,14]. However, clinical evidence from em bolization for left ventricular thrombus is much less common.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%
“…However, clinical evidence from em bolization for left ventricular thrombus is much less common. An embolic stroke complicates myocardial in farction in less than 6% of patients after an acute myocar dial infarction [13][14][15][16]. Left ventricular thrombi appear to develop on an average of 4-5 days after the myocardial infarction [17,18].…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%